ELW LP 평가제도에 변동성 활용방안 - 최영수(Young Soo Choi); 주상룡(Sang Lyong Joo); 이원창(Won Chang Lee) (한국증권학회지, 2012)
본 논문은 코스피 200 장내옵션을 이용한 변동성지수인 VKOSPI 형태의 지수 ELW 시장 변동성 지수 산출 방안을 제시하였고 장내옵션의 내재변동성과 괴리를 비교할 수 있는 지수 ELW 변동성 괴리도를 제안하여 그 특성을 실증분석하고 ELW LP(Liquidity Provider: 유동성공급자) 평가에 활용하였다. 본 논문에서 제안한 변동성지수는 장내옵션을 이용한 비교분석에서 강건함을 확인할 수 있었고ELW 자료를 이용한 분석에서 변동성지수는 행사가격 범위와 시장참여자의 호가자료에 영향을 받음을 알 수 있었다. 특히, ELW 시장 및 LP 매도호가를 이용한 변동성지수는 장내옵션을 이용한 변동성 지수에 비해 지속적으로 높게 나타나고 LP가 제공하는 매도호가/중간값 간에는 차이가 존재하나 시장 매도호가/중간값 간에는 차이가 없음을 확인할 수 있었다. 이런 차이는 LP 수익의 원천인 호가 스프레드에 기인한 것으로 판단된다. 변동성 괴리를 변동성 수준괴리에 대한 상대비율의 평균과 절대평균으로 벤치마크 대비 괴리 수준을 판단하였고 변동성 수준괴리에 대한 표준편차를 통하여 변동성의 변동을 판단하였다. ELW LP 평가제도에 대하여 본 논문에서 제안한 괴리도의 시계열 변화추이를 적용하면 현행 평가 제도는 변동성의 변동에 중점을 두고 있어 이 항목은 잘 관리되고 있음을 확인할 수 있다. 하지만 변동성 수준괴리는 지속적으로 확대되고 있으므로 ELW LP 평가제도의 내재변동성 평가항목을 내재변동성 수준괴리와 변동항목으로 세분하여 평가하기를 권고한다. This paper introduces a method to calculate ELW market volatility index, which is similar to VKOSPI obtained by using KOSPI 200 index option, and offers ELW market volatility disparity, which is used to compare the disparity between KOSPI 200 index option volatility and its ELW volatility. Using ELW volatility index and disparity, we analyze their characteristic and use them for ELW LP(Liquidity Provider) evaluation system. Our proposed volatility index is robust in comparative analysis by using KOSPI 200 option data and is affected by ELW exercise price range and ELW bid or ask price. Especially, volatility index using ELW market bid-ask price and ELW LP ask price are constantly higher than volatility index using KOSPI 200 option, and there is a difference between ask and mid price offered by ELW LP, but no differences between ask and mid price offered by market participant. This difference is due to bid-ask spread which is a ELW LP profit source. In this paper, MPD(Mean Percentage Disparity) and MAPD(Mean Absolute Percentage Disparity) are proposed to measure the mean and absolute mean of disparity level ratio from the benchmark. Also RMSE(Root Mean Square Disparity) is proposed to measure the volatility of disparity level. Our proposed measures can be applied to evaluate ELW LP evaluation system. In particular, empirical analysis shows that, due to the current LP evaluation system emphasizing the control of volatility for disparity, RMSE for ELW LP is well-managed, but MPD and MAPD are constantly expanding. Thus, we suggest to subdivide ELW LP evaluation system’s volatility sector into volatility of disparity and level of disparity. KCI Citation Count: 10